(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article contains the results of an analysis of the problem of the management of an educational institution in the conditions of application of educational innovations. The ways of increasing the efficiency of management of innovative processes in educational institutions in the context of reforming the educational space are indicated. It is acknowledged that coaching can be an important tool for influencing the results of the activity of individuals and the organization as a whole, in order to increase the effectiveness of the managerial activity of the head of the educational institution.